PENGEMBANGAN KAPASITAS KELEMBAGAAN DALAM PENGELOLAAN SAMPAH DI KABUPATEN BREBES - Evi Indriani; Hardi Warsono (Journal of Management and Public Policy, 2026)
Brebes Brebes Regency is one of the most populous areas in Central Java. With a population of 2,065,500 and a growth rate of 1.10%, this results in an annual waste generation of 372,861.55 tonnes. This situation requires an adaptive and integrated management system, given that the Kaliwlingi Landfill has become overloaded due to its open dumping system. Currently, waste management service coverage has only reached 21.38% of the target, with a daily collection volume of 225.25 tonnes. This low collection rate indicates that the majority of waste is not being managed optimally, presenting a crucial challenge in efforts to enhance the institutional capacity of waste management services in Brebes Regency. This study aims to analyse institutional capacity in waste management in Brebes Regency and to identify the factors supporting and hindering this institutional capacity. The method used is a descriptive qualitative approach with data collection techniques involving interviews and documentation. The research findings indicate that the institutional capacity for waste management in Brebes Regency remains suboptimal, as evidenced by limitations in human resources, facilities and infrastructure, as well as low levels of community participation in waste reduction and management activities. Factors supporting institutional capacity include the existence of governing regulations, conducive leadership, and a well-established work culture. Meanwhile, the inhibiting factors are that not all institutional actors are actively involved in supporting the success of waste management, which has resulted in suboptimal performance of waste management services in Brebes Regency.